Examination of the relationship between derivative financial instruments and the economic development of Lithuania - Kristina Garskaite-Milvydiene; Raimonda Martinkute-Kauliene (Contemporary Economics, 2021)
Derivative financial instruments play a major role in financial markets. However, there are rather contradictory views regarding this issue. Their impact on the financial markets, their stability and the economy have not been thoroughly examined. The aim of this paper is to analyse derivatives and the economic situation in the country and to investigate the relationship between the derivatives and the macroeconomic factors which have the greatest impact on the volume of the derivatives. The paper analyses derivatives statistics and macroeconomic indicators in Lithuania. As a result, the relationship between the derivatives and the country's macroeconomic indicators is examined by identifying the most significant factors, as the structure and volume of derivatives in different markets may be determined by different macroeconomic factors. The performed analysis and estimation have shown that foreign direct investment has the largest impact on the derivatives, their volume and structure, and average earnings have the least impact.
Keywords: F23; G01; G10; G34; 330; Derivative financial instruments (derivatives); foreign exchange transactions and interest rate derivative contracts; GDP; inflation; unemployment rate